USING BRIGHT–ENGLISH FOR BEGINNERS APPLICATION TO ENRICH STUDENTS’ VOCABULARY - Liando, Nitha V. F.; Mangare, Alfiani R. D.; Olii, Sanerita Tresnawaty (Jurnal Pendidikan Bahasa Inggris undiksha, 2021)
The main problem for Indonesian English learners is the lack of vocabulary. During the teaching and learning process, most students often need more time to complete the tasks given by the teacher. Students have to translate the text word by word because their vocabulary is limited. It takes a long time, so achieving learning objectives is less effective. In practice, language is complex for students to understand. This study aims to analyze whether the Bright – English for Beginners application can enrich students' vocabulary or not. It is quantitative research with a pre-experimental design with one group pre-test and post-test. This research was conducted on class VII students consisting of 22 students. The methods used to collect data are observation, interviews, and tests. The instruments used to analyze the data are questionnaires and question sheets in analyzing the data obtained using descriptive statistics. The study results were that there was a statistically significant difference between the pre-test (before treatment) and post-test (after treatment). The mean pre-test score was 34.62, while the mean post-test was 88.25. Post-test achievement is higher than pre-test achievement. The findings of this study reveal that the use of the Bright – English for Beginners application significantly enriches students' vocabulary. As a result, it can be concluded that the Bright – English for Beginners application effectively improves students' vocabulary.